2017
DOI: 10.1002/2017jb014376
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Dynamic Helium Release as a Tracer of Rock Deformation

Abstract: We use helium released during mechanical deformation of shales as a signal to explore the effects of deformation and failure on material transport properties. A dynamic dual-permeability model with evolving pore and fracture networks is used to simulate gases released from shale during deformation and failure. Changes in material properties required to reproduce experimentally observed gas signals are explored. We model two different experiments of $^4$He flow rate measured from shale undergoing mechanical def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The temporal scales of the processes involved not only require a high-frequency monitoring system 24,32 but also a multi-tracer approach, i.e., He, Ar and N 2 in the case of the GTS. Complementing the findings of previous experiments performed in the laboratory [17][18][19][20] , as (2020) 10:6949 | https://doi.org/10.1038/s41598-020-63458-x www.nature.com/scientificreports www.nature.com/scientificreports/ well as those advanced from large-scale observations in the context of earthquakes 5 , we interpret these anomalies as the release of radiogenic He (and Ar) stored in the rock mass that could be transported within the newly created and pre-existing fracture system. While the identification of the source of the mobilized fluids is still speculative, two complementing hypotheses on its origin are proposed: (1) radiogenic He (and Ar) accumulated in the rock matrix is released by the formation of new fracture areas; and/or (2) the shearing of pre-existing fractures induces the remobilization of stagnant fluids, with higher residence times enriched in radiogenic He and Ar, trapped in lower transmissivity zones of the fracture network.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The temporal scales of the processes involved not only require a high-frequency monitoring system 24,32 but also a multi-tracer approach, i.e., He, Ar and N 2 in the case of the GTS. Complementing the findings of previous experiments performed in the laboratory [17][18][19][20] , as (2020) 10:6949 | https://doi.org/10.1038/s41598-020-63458-x www.nature.com/scientificreports www.nature.com/scientificreports/ well as those advanced from large-scale observations in the context of earthquakes 5 , we interpret these anomalies as the release of radiogenic He (and Ar) stored in the rock mass that could be transported within the newly created and pre-existing fracture system. While the identification of the source of the mobilized fluids is still speculative, two complementing hypotheses on its origin are proposed: (1) radiogenic He (and Ar) accumulated in the rock matrix is released by the formation of new fracture areas; and/or (2) the shearing of pre-existing fractures induces the remobilization of stagnant fluids, with higher residence times enriched in radiogenic He and Ar, trapped in lower transmissivity zones of the fracture network.…”
Section: Discussionsupporting
confidence: 81%
“…Chemical anomalies created by earthquakes have been explained by the mixing of fluids from different sources (with different chemical compositions) inhibited by changes in flow pathway geometry and hydraulic properties during stress build-up and failure 15,16 . Laboratory studies have also observed the emergence of concentration anomalies in noble gases during rock deformation experiments [17][18][19][20] . The authors argued that the progressive increase in microcrack surfaces during increasing stress allows the remobilization of accumulated radiogenic gases and even prior macroscopic failure.…”
mentioning
confidence: 99%
“…These data provide information on the mechanics and timing of gas release. Previous studies have shown that helium is released during elasticity and brittle deformation from both sedimentary and crystalline rocks [2,3,35]. In this study, we show that helium and argon are released from rock salt during mechanical deformation.…”
Section: Discussionsupporting
confidence: 57%
“…These nobles gases are likely released as a result of episodic fracturing and brittle deformation in the subsurface [2,3]. Recent research has shown that radiogenic noble gases released from rocks as they are deformed can be observed [4][5][6][7][8]. Thus, monitoring noble gas release and isotopic composition could provide a new method of measuring and inferring subsurface deformation mechanics.…”
Section: Introductionmentioning
confidence: 99%